Social Media Sentiment Analysis to Measure Community Response in the Millennial Road Safety Festival Program Using TF-IDF and Support Vector Machine - Saiful Bukhori; Sonya Sulistyono; Antonius Cahya Prihandoko; Januar Adi Putra; Windi Eka Yulia Retnani; Umroh Makhmudah; Muhammad Noor Dwi Eldianto (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2020)
This Sentiment Analysis is a combination of data mining and text mining. Sentiment Analysis itself is used to process various opinions that the public or experts have given through a variety of existing media. The argument is given to a product, service, or agency. Sentiment Analysis has three types of opinions: negative opinions, positive opinions, and neutral opinions. Based on the test results, the resulting model achieves the highest accuracy of 83.33% when using 80:20 scenario data, while the lowest accuracy of 80.00% is achieved when using the 60:40 scenario data. The higher the precision that will be obtained, whereas using less training data will be slightly unstable. ABSTRAK Sentiment Analysis merupakan perpaduan dari data mining dan teks mining, dimana Sentiment Analysis sendiri digunakan untuk mengolah berbagai macam opini yang telah diberikan oleh masyarakat atau para pakar melalui berbagai media yang ada, opini tersebut diberikan untuk sebuah produk, jasa maupun sebuah instansi. Pada Sentiment Analysis terdapat 3 jenis opini, yaitu opini negatif, opini positif dan opini netral. Berdasarkan hasil pengujian, model yang dihasilkan mencapai akurasi tertinggi yaitu 83,33% saat menggunakan data skenario 80:20, sedangkan akurasi terendah 80,00% dicapai ketika menggunakan skenario data 60:40 Skenario data dapat memengaruhi tingkat akurasi semakin banyak jumlah data pelatihan yang diberikan, semakin tinggi akurasi yang akan diperoleh, sedangkan jika menggunakan lebih sedikit data pelatihan, hasilnya akan sedikit tidak stabil.